Ethnocultural transference and countertransference in psychodynamic psychotherapy in the Netherlands - Gomperts, Wouter (Psychotherapie-Wissenschaft, 2018)
In recent years, members of non-Western ethnic minorities in the Netherlands have increasingly received psychodynamic psychotherapy, up to now usually from native Dutch therapists. All the ordinary mental problems and common components of psychodynamic therapy can then acquire somewhat different contents and significance. This article is on ethnocultural transference and countertransference in the therapeutic relationship between second-generation post-migration patients with a non-Western background and native Dutch therapists.